Strategic Economic Diplomacy: ITPC Jeddah’s Impact in Advancing Indonesia’s Global Trade Agenda - Yunita, Primadiana; Pohan, Ibnu Asqori; Killian, Erza (RMPI-BRIN, 2022)
Indonesia’s economic diplomacy focuses on three main activities: trade, tourism, and investment. Indonesia has also begun to seek expansion in non-traditional markets such as the Middle East region by conducting economic diplomacy. The Indonesian government receives assistance from the Indonesian Trade Promotion Centre (ITPC) in the Middle East Region, specifically ITPC Jeddah, to facilitate the implementation of trade as a component of economic diplomacy activities. However, since COVID-19 hit, conventional diplomacy activities have shifted to digital diplomacy. Various exhibitions are conducted online; even business matching can only be done via teleconference. In addition, ITPC Jeddah has also begun to utilize social media, especially Instagram, to expand and increase awareness of the Middle East community’s superiority of Indonesian trade commodities. Through Kishan Rana’s four stages of economic diplomacy, this research explains how Indonesia’s digital economic diplomacy patterns are reviewed through the ITPC Jeddah Instagram account. This research will later produce how ITPC Jeddah conducts its digital diplomacy and determine whether ITPC has used its social media optimally as a tool for digital economic diplomacy.